A high density two-dimensional electron gas in an oxide heterostructure on Si (001) - Jin, Eric N; Kornblum, Lior; Kumah, Divine; Zou, Ke; Broadbridge, Christine; Ngai, J H; Ahn, C H; Walker, Fred (APL Materials, 2014)
We present the growth and characterization of layered heterostructures comprised of LaTiO3 and SrTiO3 epitaxially grown on Si (001). Magnetotransport measurements show that the sheet carrier densities of the heterostructures scale with the number of LaTiO3/SrTiO3 interfaces, consistent with the presence of an interfacial 2-dimensional electron gas (2DEG) at each interface. Sheet carrier densities of 8.9 × 1014 cm-2 per interface are observed. Integration of such high density oxide 2DEGs on silicon provides a bridge between the exceptional properties and functionalities of oxide 2DEGs and microelectronic technologies. © 2014 Author(s).
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-040-511-772-110 tex.type: [object Object]
Keywords: dept.phy

Valence electron energy-loss spectroscopy of ultrathin SrTiO3 films grown on silicon (100) single crystal - Su, Dong; Yang, Bo; Jiang, Nan; Sawicki, Monica; Broadbridge, Christine; Couillard, M; Reiner, James W; Walker, Fred; Ahn, C H; Zhu, Yimei (Applied Physics Letters, 2010)
Valence electron energy-loss spectroscopy is used to investigate the plasmon excitations of ultrathin SrTiO3 sandwiched between amorphous Si and crystalline Si. Two plasmon excitations were observed, one at 15.8 eV and the other at 28.7 eV. Our calculations, based on dielectric-function theory, suggest that the former peak originates from the coupling of the Si layers and is related to the geometry of the structure, and the latter peak results from the SrTiO3 bulk plasmon after a redshift. Our findings demonstrate the value of valence electron energy-loss spectroscopy in detecting a local change in the effective electron mass. © 2010 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-562-101-735-184 tex.type: [object Object]
Keywords: Amorphous Si; Amorphous silicon; Crystalline Si; Dissociation; Electron energy loss spectroscopy; Electron scattering; Electrons; Function theory; Plasmon excitations; Plasmons; Red shift; Si layer; Silicon (100); Silicon wafers; Single crystals; SrTiO; Strontium alloys; Ultra-thin; Valence electron energy-loss spectroscopies; dept.phy